Reducing low-value imaging - stakeholders' assessment of an intervention to improve imaging services - Elin Kjelle; Ingrid Øfsti Brandsæter; Eivind Richter Andersen; Bjørn Morten Hofmann (BMC, 2024)
Abstract Background An intervention to reduce low-value magnetic resonance imaging (MRI) was designed and implemented in private imaging centres in Norway in October 2022. The intervention used return letters for poor referrals of MRI of the lower back, brain and knee at private imaging centres in Norway. The study aimed to investigate key stakeholders' experiences and assessment of the intervention and the specific research questions were: • How many return letters were sent during the study period? • What were the medical directors' and managers' experiences with and reflection on success factors for the intervention implementation and using return letters? Methods The number of return letters sent was collected directly from Norway's two main private imaging providers. Two semi-structured individual interviews were conducted with the medical directors of the imaging providers, as well as two focus group interviews with nine managers from the various private imaging centres operated by the two imaging providers. Results In total, 1,182 return letters were sent for patients undergoing one of the three types of MRI examinations, and the number of return letters was highest at the beginning of the intervention. The interview analysis resulted in five categories: general experience, anchoring, organisation, return letter procedure and outcome. Sufficient information, anchoring and support were identified as crucial success factors. Conclusions This study provides insights into the practical and crucial details of implementing interventions to reduce low-value imaging. The intervention was generally well received, and the high initial number of return letters decreased rapidly over the course of the study. Several key success factors were identified.